Hong Kong's export-propelled growth - Y. C. Jao (Intereconomics, 1974)
Hong Kong's metamorphosis from an entrepot to an industrial economy during the past quarter of a century gives a good example of how a developing country can achieve remarkable growth through international trade.
Keywords: 330; Hong Kong